2008
DOI: 10.1001/archinte.168.15.1609
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Metabolically Benign Obesity in Humans

Abstract: Background: Obesity represents a risk factor for insulin resistance, type 2 diabetes mellitus, and atherosclerosis. In addition, for any given amount of total body fat, an excess of visceral fat or fat accumulation in the liver and skeletal muscle augments the risk. Conversely, even in obesity, a metabolically benign fat distribution phenotype may exist.Methods: In 314 subjects, we measured total body, visceral, and subcutaneous fat with magnetic resonance (MR) tomography and fat in the liver and skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
616
9
38

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 909 publications
(704 citation statements)
references
References 48 publications
27
616
9
38
Order By: Relevance
“…Obese participants who are free from cardiometabolic disease risk factors are termed “metabolically healthy obese.”9, 26 The existence of the metabolically healthy obese condition has been controversial27, 28, 29, 30; however, we have recently added some clarification to this issue by pointing out that conclusions rest heavily on the definition of metabolically healthy obese 31. We4, 5, 10 and others12, 13, 14 have shown that 1 or 2 metabolic syndrome traits confer increased risk of diabetes mellitus and CVD outcomes and that such persons are relatively insulin resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Obese participants who are free from cardiometabolic disease risk factors are termed “metabolically healthy obese.”9, 26 The existence of the metabolically healthy obese condition has been controversial27, 28, 29, 30; however, we have recently added some clarification to this issue by pointing out that conclusions rest heavily on the definition of metabolically healthy obese 31. We4, 5, 10 and others12, 13, 14 have shown that 1 or 2 metabolic syndrome traits confer increased risk of diabetes mellitus and CVD outcomes and that such persons are relatively insulin resistant.…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype is referred in the literature as "metabolically healthy obesity" (MHO) and may account for around 30% of the obese population [60]. Interestingly, the MHO phenotype is characterized by a more favourable body fat distribution with lower visceral fat and greater subcutaneous fat [42], by a lower ectopic fat depot in the liver [61], and by a less inflammatory profile with lower levels of circulating inflammatory markers [14,42] compared to unhealthy obese phenotype. We have recently reported that the visceral adipose tissue of MHO phenotype is associated with lower activation of the NLRP3 inflammasome in infiltrating macrophages, and with a more favourable inflammatory and immunological profile compared to that of unhealthy obese phenotype [33] (Figure 3).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, compared with their peers who are MAO, individuals with MHO have lower risk of all-cause and cause-specific mortality [2][3][4] . Furthermore, studies suggest that individuals with MHO have similar insulin sensitivity to lean individuals, as well as lower liver fat content and lower intimal-medial thickness of the carotid artery compared with individuals who are MAO 5,6 . Agreement on a universally accepted definition of MHO, however, would improve the design of future studies and would facilitate comparisons between studies.…”
Section: Standfirst (51 Words)mentioning
confidence: 99%